The epidemiology of carbapenemases in Latin America and the Caribbean (2020)
Introduction: Enterobacteriaceae, Pseudomonas spp., and Acinetobacter spp. infections are major causes of morbidity and mortality, especially due to the emergence and spread of β-lactamases. Carbapenemases, which are β-lactamases with the capacity to hydrolyze or inactivate carbapenems, have become a serious concern as they have the largest hydrolytic spectrum and therefore limit the utility of most β-lactam antibiotics. Areas covered: Here, we present an update of the current status of carbapenemases in Latin America and the Caribbean. Expert commentary: The increased frequency of reports on carbapenemases in Latin America and the Caribbean shows that they have successfully spread and have even become endemic in some countries. Countries such as Brazil, Colombia, Argentina, and Mexico account for the majority of these reports. Early suspicion and detection along with implementation of antimicrobial stewardship programs in all healthcare settings are crucial for the control and prevention of carbapenemase-producing bacteria.